Performance Investigation of Dynamic Characteristics of Power Semiconductor Diodes - Špánik, P.; Šul, R.; Frívaldský, M.; Drgoňa, P.; Kandráč, J. (Elektronika ir Elektrotechnika, 2010)
Utilization of SiC SBD diodes in DC-DC converter applications is discussed. First reverse recovery effect of various diodes’ structures and its elimination is being described. Experimental measurements have been done and consequently data were converted into continuous form for graphic interpretation in dependence on switching frequency, supply voltage and load current. Accordingly, the utilization of new progressive materials of power SBD diodes on SiC technology is being described, whereby measurements were done also at higher (150C) temperatures. This measurements show key differences in dynamic characteristic between each diodes and therefore proper selection of diode and optimization of power supply should be done. It is concerned SiC SBD diode structures versus Si UltraFast and HyperFast diodes rated for 600V. Ill. 9, bibl. 22 (in English; summaries in English, Russian and Lithuanian).